Cyber Sexual Harrasment dalam Media Sosial Instagram - Puput Mulyani; Rini Sulastri (UIN Sunan Gunung Djati Bandung, 2024)
Based on several studies, most of the internet is used to access social media, for example Instagram which is used by Indonesian people. This will of course have positive and negative impacts, one of the positive impacts is that it makes it easier for people to communicate. Meanwhile, the negative impact is that it brings new problems, namely online-based crimes, one of which is cyber sexual harassment. Many individuals don't know what forms of cyber sexual harassment exist on Instagram. Therefore, researchers will describe the forms of cyber sexual harassment and the factors that cause cyber sexual harassment based on Erving Goffman's dramaturgical theory. The research method used is descriptive qualitative. The research results found 5 forms of cyber sexual harassment on Instagram, namely (1) spamming, (2) visual harassment, (3) verbal harassment, (4) doxing and (5) fake accounts. The factor causing cyber sexual harassment on Instagram social media is based on Erving Goffman's theory, namely, imperfect self-control in expressing oneself creates gaps in themselves to become victims of cyber sexual harassment